The Role of Satpol PP in Handling Buskers and Beggars in Batam City - Lumbantobing, Devi Emelda Br; Maileni, Dwi Afni; Bhakti, Rizki Tri Anugrah; Hutasoit, Isfandir (Dinasti Research, 2026)
This study aims to analyze the role of the Batam’s Satpol PP in handling buskers, vagrants and beggars from an administrative law perspective. The study focuses on operational actions, cross-agency coordination patterns, and implementation constraints that affect the sustainability of enforcement outcomes in public spaces. The study employed a qualitative approach with a case study strategy. Data were collected through semi-structured interviews, field observations, and reviews of policy and administrative documents, analyzed using thematic analysis, strengthening trustworthiness through source and technique triangulation, audit trails, and adequate context descriptions. The results indicate that enforcement practices in Batam utilize a hybrid enforcement pattern, combining persuasive approaches, administrative actions, and situational enforcement according to the field context. Satpol PP plays a crucial role as a liaison between agencies, but its long-term effectiveness is limited by inconsistent referral channels, varying social service capacity, and a weak post-enforcement follow-up mechanism. The findings emphasize that the success of enforcement is not solely measured by the immediate restoration of order, but rather by the legality of actions, procedural proportionality, quality of coordination, and the sustainability of social impacts. The research contributes to strengthening administrative law studies by showing that effective handling requires integration between norm enforcement, social protection, and the design of more institutionalized cross-agency collaboration.